Early Chinese and Greek Accounts of Chance and Randomness - Raphals, Lisa (International journal of divination and prognostication, 2024)
Chance was an important concept in both early China and Greece. But what in a contemporary context is a largely value-neutral scientific concept arose in ethical, philosophical, and political contexts in these two cultures, and took very different forms in each. I examine four examples that demonstrate important differences in philosophical, ethical and political concepts and also in social institutions. I argue that Chinese and Greek ideas of chance did not receive extensive scientific development, but they fundamentally informed their respective cultures in ways that were important and very different from each other: Greek ideas of quality under law and Chinese ideas of sagacity and effective rule.